Intestinal fibrosis associated with inflammatory bowel disease: Known and unknown - Yao Zhang; Haiming Zhuang; Kai Chen; Yizhou Zhao; Danshu Wang; Taojing Ran; Duowu Zou; Yuanyuan Ji (Chinese Medical Journal)
Abstract. Intestinal fibrosis is a major complication of inflammatory bowel disease (IBD), leading to a high incidence of surgical interventions and significant disability. Despite its clinical relevance, no targeted pharmacological therapies are currently available. This review aims to explore the underlying mechanisms driving intestinal fibrosis and address unresolved scientific questions, offering insights into potential future therapeutic strategies. We conducted a literature review using data from PubMed up to October 2024, focusing on studies related to IBD and fibrosis. Intestinal fibrosis results from a complex network involving stromal cells, immune cells, epithelial cells, and the gut microbiota. Chronic inflammation, driven by factors such as dysbiosis, epithelial injury, and immune activation, leads to the production of cytokines like interleukin (IL)-1β, IL-17, and transforming growth factor (TGF)-β. These mediators activate various stromal cell populations, including fibroblasts, pericytes, and smooth muscle cells. The activated stromal cells secrete excessive extracellular matrix components, thereby promoting fibrosis. Additionally, stromal cells influence the immune microenvironment through cytokine production. Future research would focus on elucidating the temporal and spatial relationships between immune cell-driven inflammation and stromal cell-mediated fibrosis. Additionally, investigations are needed to clarify the differentiation origins of excessive extracellular matrix-producing cells, particularly fibroblast activation protein (FAP)+ fibroblasts, in the context of intestinal fibrosis. In conclusion, aberrant stromal cell activation, triggered by upstream immune signals, is a key mechanism underlying intestinal fibrosis. Further investigations into immune–stromal cell interactions and stromal cell activation are essential for the development of therapeutic strategies to prevent, alleviate, and potentially reverse fibrosis.